Hubungan Antara Karakteristik Individu dan Manual Material Handling dengan Keluhan Muskuloskeletal Akibat Kerja (The Relationship Between Individual Characteristics and Manual Material Handling With Musculosceletal Complaints Due To Work) - Ahmad Mushthofa As'Adi; Anita Dewi Prahastuti Sujoso; Irma Prasetyowati (Pustaka Kesehatan, 2014)
Occupational Health and Safety (K3) is one of the requirements to improve employeeproductivity, beside that the Occupational Health and Safety is every labor rights.Conveyances Workers in Tanjung Market Jember generally works using their body as a toolto carry goods, and done in a long time and repeatedly. It is potential to experience workrelatedmusculoskeletal complaints. The aim of this study was to analyze the relationshipbetween individual characteristics and Manual Material Handling with musculoskeletalcomplaints due to work. The method used was cross sectional with the respondents of 60people, using lambda association test analysis techniques. The results of data analysisshowed no relationship between age (ρ = 0.0001), and nutritional status (BMI) (ρ = 0.041),with musculoskeletal complaints due to work. While the smoking habit (ρ = 0.249) andworking period (ρ = 0.170) showed no relationship with musculoskeletal complaints due towork, and for manual material handling (MMH) (ρ = 0.018) by using the method of RWL andLI measurement indicated there was a relationship between manual material handling withmusculoskeletal complaints due to work. Based on these results the government isexpected to take action to prevent the occurrence of occupational diseases, especially inthe informal sector.Keywords: Individual Characteristics, Manual Material Handling, MusculoskeletalComplaints, Conveyances Workers.